Menstrual irregularity and mental health problems among Bangladeshi adolescent girls: Prevalence and associated factors of mental health problems and menstrual irregularity among Bangladeshi adolescent girls - Mohosina Akter; Md. Safaet Hossain Sujan; Muhammad Ramiz Uddin; Lakshmi Rani Kundu (Health Prospect, 2025)
Background:  Despite being more prevalent in adolescent girls, menstrual irregularity remains a poorly treated health concern in developing countries like Bangladesh. Moreover, this notable health issue disproportionately impacts the mental well-being of adolescents. Interestingly, there is a bidirectional relationship between adolescents' mental health and menstrual irregularity. This study seeks to explore the prevalence and associations of mental health problems and menstrual irregularity among adolescent girls. Methods: A cross-sectional face-to-face survey was conducted on 501 adolescent girls from February to April 2023. Data on demographics, menstrual irregularities, and mental health issues were collected using a structured questionnaire. The questionnaire included assessments such as the Patient Health Questionnaire (PHQ-9), Generalized Anxiety Disorder (GAD-7), and UCLA Loneliness (UCLA-3) scales. Statistical analyses, such as the chi-squared test and logistic regression, were employed to explore potential correlations between the variables. Results: The mean age of the respondents was 15.61 years. The prevalence rates of various issues were as follows: menstrual irregularity (28.9%), psychological stress (38.9%), suicidal thoughts (6.6%), depression (25.5%), anxiety (24.6%), and loneliness (20%). Among the participants, those who experienced menstrual irregularity frequently were found to have higher rates of severe depression, anxiety, and loneliness. Conclusion: The latest discoveries have brought to light a significant prevalence of menstrual irregularities among adolescent girls, leading to severe mental health issues. Parents and health service providers must take proactive measures to curb the occurrence of menstrual irregularities in this group. Failing to do so could put them at risk of compromised reproductive health and mental well-being.